VD_FINDINFO Arrêt / 2016 / 219 vom 9. März 2016 - VD Tribunal cantonal (2016)
CURATELLE, CURATELLE DE GESTION, CURATELLE DE REPRÉSENTATION, CHOIXEN GÉNÉRAL, CURATEUR | 393 ch. 1 CC, 394 al. 1 CC, 395 al. 1 CC, 40 LVPAE